A study of early experience with the use of buccal mucosa for substitution urethroplasty - Rajasekar Maruthamuthu; Pugazhenthi Periasamy; Jayaprakash Narashimman; Kuladeep Vankadara (Asian Journal of Medical Sciences, 2023)
Background: The long-term results of internal urethrotomy are poor in stricture urethra. It requires repeated procedures followed up with repeated dilatation. Suprechko in 1886, was the first to describe the use of buccal mucosal graft (BMG). The new technique of dorsal on-lay graft Urethroplasty described by Barbagli in 1995, has been greeted with great amount of enthusiasm through the world. Aims and Objectives: The aim of the study is to evaluate the efficacy of buccal mucosa graft in stricture urethra at our centre. The main objective of this study is to assess early complications in buccal mucosal Urethroplasty. Materials and Methods: It is a prospective study conducted at Stanley medical college, Chennai from October 2011 to February 2013. A total of 13 patients were enrolled in the study. Results: Out of 13 patients, 9 patients underwent dorsal on-lay BMG. 3 patients underwent dorsal on-lay+ventral meatotomy. 2 patients underwent dorsal on-lay+meatoplasty. Only two patients developed immediate post-operative wound infection. One patient developed 1 cm penile skin necrosis at ventral aspect of penis. None of the patient developed significant complications. Conclusion: Dorsal on-lay is the preferred form of graft placement. BMG is the ideal substitute for urethra, especially in medium length urethral stricture. Oral cavity donor site had no significant complications. Failure rate was 15.38%, so dorsal on lay technique is ideal for urethral stricture with longer follow up required.